Determination of Orthodontic Treatment Need for Individuals in Pubertal Growth Period and Effects of Different Variables on the Treatment Needs with Using the ICON Index - Hasan Kamak; İbrahim Erhan Gelgör; Hakan Keklik (Galenos Yayinevi, 2012)
Aim:To evaluation of orthodontic treatment need for individuals who are in pubertal growth period with using the ICON index and whether treatment need change according to gender, dental, sagittal and vertical skeletal malocclusions.Subjects and Method:In this study, pretreatment orthodontic casts and panoramic films of 138 patients (75 females, 63 males and mean age 13.8 ± 1,2) were investigated by using ICON index.Results:91 of 138 patients (%65,9) were found to be need for orthodontic treatment. Although it is not statistically significant, females in genders (%69,3), Class III patients in dental malocclusions % 71,4), and Class I and Class III anomalies in sagittal skeletal malocclusions were found higher than the others. Also, in vertical skeletal malocclusions, orthodontic treatment needs of hyper-diverjant patients % 79,3) were found statistically higher than the others.Conclusion:The majority of individuals who were in pubertal growth period were female (% 54,3), dental Class II (% 70,3), skeletal Class I malocclusion (%55,8) and normo-diverjant (%47,8). It was seen that when the vertical direction growth increased, the need for orthodontic treatment increased. As a result, studies about indexes should be done for comparison, sharing and proliferation of new information, and patients determination for orthodontic treatment should be done according to treatment needs rather than Angle classifications.